The Vegetation Diversity of the Growth Rate Stand in The PBPH PT. Hutan Mulya Central Kalimantan’s - Hardiansyah, Gusti; Fitriani, Afni; Yani, Akhmad (Media Konservasi, 2024)
PT Hutan Mulya is one of the companies engaged in natural forest management, carrying out logging activities that cause changes in the value of species diversity in the remaining stands (LoA). There are 651 individuals of 87 plant species in the LoA area (2016 and 2016) and 63 plant species in virgin forest areas, so there are a total of 32 plant groups. The highest Importance Value Index is found in Meranti Merah (Shorea leprosula Miq) and Suhi (Shorea atrinervosa Symington) in virgin forest areas, while in the LoA area it is dominated by the Jambuan (Syzygium Gaertn) species because it is a source of animal feed and is not produced by companies. The diversity index of tree species, poles, and saplings in virgin forest is high (>3.00), whereas in the LoA area (2016 and 2022), the level of trees is high (>3.00), the level of poles is medium (1.00–3, 00), and the level of saplings for LoA 2022 is low (1.00<). Meanwhile, the virgin forest similarity index and LoA (2016 and 2022) are in the same or medium category, between 0.31 and 1.00.